Drug Delivery for the Retina and Posterior Segment Disease (Springer International Publishing, 2018)
This book addresses the issues relating to a wide variety of ocular diseases from which millions of people suffer. Long-term challenges include visual impairment and ocular blindness. Certain ocular diseases are quite rare, whereas others, such as cataracts, age-related macular degeneration (AMD), and glaucoma, are very common, especially in the aging population. A rapid expansion of new technologies in ocular drug delivery and new drug candidates, including biologics, to treat these challenging diseases in the retina and posterior segments of the eye have recently emerged. These approaches are necessary because the eye has many unique barriers to drug delivery. Thus, this timely reference Drug Delivery for the Retina and Posterior Segment Disease compiles and analyzes recent advances in the research and development of drug delivery systems for retina and posterior segment diseases of the eye, with an emphasis on the use of implantable devices, iontophoresis as well as micro- and nanoparticles. .